Nonalcoholic fatty liver disease and Type 2 diabetes mellitus - Mala Dharmalingam; P Ganavi Yamasandhi (Indian Journal of Endocrinology and Metabolism, 2018)
Type 2 diabetes mellitus (T2DM) and nonalcoholic fatty liver disease (NAFLD) commonly exist together. It has been regarded as a manifestation of the metabolic syndrome. The presentations of NAFLD range from simple steatosis (NAFL), nonalcoholic steatohepatitis (NASH), and cirrhosis. NAFLD has a prevalence of 70% among T2DM patients. Overweight/obesity and insulin resistance (IR) have been strongly linked with NAFLD. Noninvasive assessment and staging of disease are based on clinical parameters such as age, sex, liver function test, platelet count, lipid profile, BMI, and imaging modalities such as USG, transient elastography (TE), and magnetic resonance imaging mass spectroscopy. Such clinical scoring systems and TE are useful in the early detection of NAFLD and predicting fibrosis. The principle behind the management of NAFLD with T2DM involves an indirect effect through improvement in IR and glycemia and thus is used for the treatment of T2DM as well.